Presenting Islam in the West - Abdul Ghafar Don, (Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2016)
Presenting Islam covering both aspects; the message of Islam a methodology of way of delivering the message. This article reviewing the book title “Presenting Islam in the West” by Daud R.Matthews, the Anglican convert to Islam. His experienced of being grown in United Kingdom and serving in Saudi Arabia provided him sufficient knowledge on culture of both tradition, Islam and the West. This book of “Presenting Islam in the West” has revealed the knowledge of the author the reality of da’wah, its nature and methodology.